Training Need Assessment and Impact of Training on Women Dairy Farmers - Saroj Kumari , Nishi Sethi , J. S. Malik Vinay Mehala; Vikram Yogi (Indian Journal of Extension Education, 2017)
The present study was conducted in Hisar district of Haryana state. From Hisar district, two blocks Adampur and Hisar-I were selected randomly. From selected blocks, two villages, namely Siswal from Adampur and Dabra from Hisar-1 were selected by random technique. From each selected village, 50 women were selected randomly, thus making a total sample of 100 women. From selected villages, 20 women who were interested in training in dairy farming were selected purposively. Majority of the respondents were of middle age, illiterate, married and belonged to joint family. Eighty-four per cent respondents had no social participation and had small herd size. Most of the respondents (25%) had medium land holding and lived in pucca houses. Training need score was obtained highest for the task housing management of cattle shed (mean 76.83 and rank-I), followed by animal health, watering, wallowing and bathing, breeding, post-parturition care, bedding, care and management of calves, feeding, marketing, farm management and accounting and milking and milk product preparation ranked from II to XI, respectively. Similarly, training need was high for animal health (rankedII) but dairy farm women had high knowledge (74.1) and low difficulty (2.19). It was surprise to see that after computing frequency, importance, difficulty and knowledge of last ranks were given to farm management and accounting (X rank) and milking and milk product preparation (XI rank) but highest learning difficulty by dairy farm women was perceived for these components. It was also interesting to note that negligible percentage of respondents performed tasks of dairy farm management, accounting and marketing where money matters were involved.